Perceived fairness of employee drug testing as a predictor of employee attitudes and job performance. - Konovsky, Mary A.; Cropanzano, Russell (Journal of Applied Psychology, 1991)
Although management of drug testing programs is becoming a critical organizational issue, no systematic conceptual framework has been applied to the study of employee reactions to drug testing. In this study an organizational justice framework was used to explain and predict the relationships among two types of justice (procedural justice and outcome fairness) employee attitudes (job satisfaction, commitment, and management trust), and behavior (turnover intentions and performance). Survey data from 195 employees in a pathology laboratory indicated that justice predicts employee attitudes and performance. Specifically, procedural justice, but not outcome fairness, predicted all 5 criterion variables. These results demonstrate the importance of procedural justice perceptions for predicting employee reactions to drug testing programs.